Whole blood interleukin-2 release test to detect and characterize rare circulating gluten-specific T cell responses in coeliac disease. (28th February 2021) - Anderson, R P; Goel, G; Hardy, M Y; Russell, A K; Wang, S; Szymczak, E; Zhang, R; Goldstein, K E; Neff, K; Truitt, K E; Williams, L J; Dzuris, J L; et al.
Summary: Whole blood cytokine release assays (CRA) assessing cellular immunity to gluten could simplify the diagnosis and monitoring of coeliac disease (CD). We aimed to determine the effectiveness of electrochemiluminescence CRA to detect responses to immunodominant gliadin peptides. HLA-DQ2·5 + CD adults (cohort 1, n = 6; cohort 2, n = 12) and unaffected controls (cohort 3, n = 9) were enrolled. Cohort 1 had 3-day gluten challenge (GC). Blood was collected at baseline, and for cohort 1 also at 3 h, 6 h and 6 days after commencing 3-day GC. Gliadin peptide-stimulated proliferation, interferon (IFN)-γ enzyme-linked immunospot (ELISPOT) and 14- and 3-plex electrochemiluminescence CRA were performed. Poisson distribution analysis was used to estimate responding cell frequencies. In cohort 1, interleukin (IL)-2 dominated the gliadin peptide-stimulated cytokine release profile in whole blood. GC caused systemic IL-2 release acutely and increased gliadin peptide-stimulated IFN-γ ELISPOT and whole blood CRA responses. Whole blood CRA after GC was dominated by IL-2, but also included IFN-γ, C-X-C motif chemokine ligand 10/IFN-γ-induced protein 10 (CXCL10/IP-10), CXCL9/monokine induced by IFN-γ (MIG), IL-10, chemokine (C-C motif) ligand 3/macrophage inflammatory protein 1-alpha (CCL3/MIP-1α), TNF-α and IL-8/CXCL8. In cohorts 2 and 3, gliadin peptide-stimulated whole blood IL-2 release was 100% specific and 92% sensitive for CD patients on a gluten-free diet; the estimated frequency of cells in CD blood secreting IL-2 to α-gliadin peptide was 0·5 to 11 per ml. Whole blood IL-2 release successfully mapped human leucocyte antigen (HLA)-DQ2·5-restricted epitopes in an α-gliadin peptide library using CD blood before and after GC. Whole blood IL-2 release assay using electrochemiluminescence is a sensitive test for rare gliadin-specific T cells in CD, and could aid in monitoring and diagnosis. Larger studies and validation with tetramer-based assays are warranted. Graphical Abstract: